Where Is the Market? Evidence from Cross-Listings in the United States - Halling, Michael; Pagano, Marco; Randl, Otto; Zechner, Josef (Review of Financial Studies, 2008)
We analyze the location of stock trading for firms with a US cross-listing. The fraction of trading that occurs in the United States tends to be larger for companies from countries that are geographically close to the United States and feature low financial development and poor insider trading protection. For companies based in developed countries, trading volume in the United States is larger if the company is small, volatile, and technology-oriented, while this does not apply to emerging country firms. The domestic turnover rate increases in the cross-listing year and remains higher for firms based in developed markets, but not for emerging market firms. Domestic trading volume actually declines for companies from countries with poor enforcement of insider trading regulation.